Mortality Pattern among Poultry Stock Reared under Intensive Management in Sub temperate Condition of Himachal Pradesh - Dinesh, Krishanender; Sankhyan, V.; Thakur, D.; Suman, M.; Sharma, A.; Bhardwaj, N. (International Journal of Livestock Research, 2021)
A study was undertaken to assess mortality pattern among poultry birds across different season maintained at CSK Himachal Pradesh Agricultural University Poultry Farm, Palampur under intensive management system. Data on mortality were collected from mortality records maintained at University Poultry Farm, Palampur. The four different types of birds were reared viz. Dahlem Red (DR), Native (N), cross of Dahlem Red and Native (DN), and cross of DN with DR (DND). A total of 641 birds were subjected for necropsy examinations at the Department of Veterinary Pathology, Palampur. Coccidiosis (33.54%), enteritis (12.16%), chilling (10.61%), ascaridiasis (10.29%) and egg blockage (9.82%) were major cause of mortality among poultry stocks. Seasonal disease incidence revealed that during winter chilling, enteritis and omphalitis were major diseases prevalent. In summers, vent pecking and coccidiosis were observed to be highest and ascaridiasis, coccidiosis, omphalitis and egg-bound condition were found to be major cause of mortality in rainy season. Overall mortality rate was reported to be highest in rainy (41.49%), followed by winter (34.32%) and summer season (24.18%). Age wise study exhibited that major cause of mortality in starter birds were chilling, omphalitis and coccidiosis. Among growers, coccidiosis was found to be the main cause of mortality. In layers, egg blockage, liver rupture, vent pecking and enteritis were more prevalent. Overall, mortality percentage was observed to be highest in DR birds (57.72%), followed by DND (15.28%), Native (13.88%) and DN (13.10%).